Experimental Afla and Ochratoxin Induced Mixed Mycotoxicosis in Broilers and its Amelioration with Herbomineral Toxin Binder ‘Toxiroak Gold’ - Sawarkar, A.R.; Sonkusale, P.M.; Kurkure, N.V.; Jangade, C.R.; Maini , S.; Ravikanth, K. (International Journal of Poultry Science, 2011)
A study was conducted in 75 dayold Vencobb broiler chicks to evaluate toxic effects of aflatoxin B1 and ochratoxin A and efficacy of herbomineral toxin binder product (Toxiroak Gold) in preventing co-mycotoxicosis. Chicks were randomly divided into three groups of 25 each. Group I served as healthy control (C) and given standard basal ration and no treatment, Group T0 and T1 comprised healthy birds fed standard basal diet and mycotoxicated with 100 ppb each of aflatoxin B1 and ochratoxin A from 0-42 days. Group T0 is not given any treatment and served as positive control; however, mycotoxicated group T1 was administered herbomineral toxin binder product Toxiroak Gold@1kg/tonne of feed for 6 weeks. Mycotoxin adversely affected body weight gain, feed consumption, feed efficiency, haematobiochemical profile. However, supplementation of herbomineral toxin binder feed supplement has provided amelioration in mixed mycotoxicosis in broilers.